Beautiful and compulsive. An analysis of the sinister poetry of Alejandra Pizarnik (1962-1968) - Yrigoyen Arbulú, María del Carmen (2023)
The article analyzes, from the perspective of compulsive beauty, a set of poems that the Argentinian author Alejandra Pizarnik published between 1962 and 1968, and that appear in Árbol de Diana (1962), Los trabajos y las noches (1965) and La extracción de la piedra de la locura (1968). To accomplish this, we will identify the main uncanny elements that populate Pizarnik’s poetic ecosystem such as mirrors, shadows and the wind. The first two imply a sort of unfolding of the  poetic voice; meanwhile the wind is a source of great contradiction by bringing together both erotic and thanatic drives. In this analysis we will observe these elements from the perspective of the sinister and the concept of compulsive beauty, which are explained by the American critic Hal Foster in his book Compulsive Beauty (1979), which is based on Sigmund Freud and André Bretón’s theoretical postulates about the unconscious and art, respectively.